Contextual Teaching and Learning Model Assisted by Zoom Cloud Meetings: The Impact on Students' Critical Thinking Skills - Sari, Diana Permata; Puspita, Laila; Handoko, Akbar (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2021)
This research aimed to investigate the influence of the Contextual Teaching and Learning (CTL) model assisted by Zoom Cloud Meeting on learners' critical thinking skills. This research employed a quasi-experimental design. The population of the study was all tenth graders of MAN 2 Tulang Bawang Barat. The samples were class X MIA 2 as the experimental class and class X MIA 3 as the control class. Tests were utilized as the data collecting technique. The researchers performed the normality and homogeneity tests on the research data before performing the independent sample t-test as the hypothesis test. Based on the test results on the Pre-test and Post-test data, the N-gain values tested using the t-test obtained a significance value (2-tailed) of 0, 00. The Contextual Teaching and Learning model assisted by Zoom Cloud Meeting improved students' critical thinking skills. Based on the research, the Contextual Teaching and Learning assisted by Zoom Cloud Meeting could improve students' critical thinking skills.